COVID-19 Impact on Rural Men and Women in Rwanda, Round 1 - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
This dataset is the result of a phone survey set up to measure the impact of COVID-19 on rural people in Rwanda. The impact of COVID-19 can affect women and men in different ways: as an income shock (directly or indirectly); as a health and caring shock; as a shock of mobility (affecting access to water, food, firewood, schooling); and as a risk of increased domestic conflict and violence. To capture these various effects on household welfare, this phone survey was conducted with (around) 500 individuals randomly drawn from an existing list of phone numbers collected from previous household surveys with 178 women and 322 men. At the time of data collection, COVID-19 cases had considerably risen in Rwanda. The focus was on the socioeconomic impacts of COVID-19 on work and income; food and nutrition security; mobility and migration; household conflicts during the pandemic and access to services. The same individuals were also interviewed during other rounds to generate a longitudinal panel allowing for analysis of the impact of COVID-19 through time.